Review of a Decade of Research on Disordered Anderson Localizing Optical Fibers - Mafi, Arash; Ballato, John (Frontiers in Physics, 2021)
Nearly a decade ago, transverse Anderson localization was observed for the first time in an optical fiber with a random transverse refractive index profile. This started the development of a whole new class of optical fibers that guide light, not in a conventional core-cladding setting based on total internal reflection, but utilizing Anderson localization, where light can guide at any location across the transverse profile of the fiber. These fibers have since been used successfully in high-quality endoscopic image transport. They also show interesting nonlinear and active (lasing) properties with promising applications. This review will cover a brief history of these fibers with personal accounts of the events that led to their development in our research groups. It will then follow with recent progress and future perspectives on science and applications of these fibers.